1998
DOI: 10.1038/emm.1998.26
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of brain-specific transglutaminases from rat

Abstract: The relevance of transglutaminases with neural function and several disorders has been emphasized recently. Especially, many polypeptides associated with neurodegenerative diseases are suggested to be putative transglutaminase substrates such as amyloid protein of Altzheimer's disease, microtubule-associated proteins and neurofilaments, etc. In addition, the CAG repeated gene products with probable polyglutamine tract, putative transglutami-nase substrates, were identified in several neuro-degenerative disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Many previous studies have been used different types of ion-exchange chromatography (SP-Sepahrose, DEAE-cellulose, Q Sepharose and DEAE-Sepharose) for purification of TGase (Ha and Iuchi, 1997;Kumazawa et al, 1997). The current study was in agreement with Goldsmith and Martin, (1995) and Kwak et al, (1998). And also the present study for purification of TGase by gel filtration Sephadex G 100 was in agreement with Folk, (1970); Tokunaga and Iwanaga (1993) and El Hofy et al, (2014).…”
Section: Transglutaminase Purificationsupporting
confidence: 86%
“…Many previous studies have been used different types of ion-exchange chromatography (SP-Sepahrose, DEAE-cellulose, Q Sepharose and DEAE-Sepharose) for purification of TGase (Ha and Iuchi, 1997;Kumazawa et al, 1997). The current study was in agreement with Goldsmith and Martin, (1995) and Kwak et al, (1998). And also the present study for purification of TGase by gel filtration Sephadex G 100 was in agreement with Folk, (1970); Tokunaga and Iwanaga (1993) and El Hofy et al, (2014).…”
Section: Transglutaminase Purificationsupporting
confidence: 86%
“…Ion-exchange chromatography, such as DEAE-Sepharose, DEAE--cellulose, QSepharose, and SP-Sepharose, have been used to purify other TGase [Tokunaga and Iwanaga 1993, Ha and Iuchi 1997, Kumazawa et al 1997. The elution profi le from DEAE-Sephadex A-50 chromatography of rosemary TGase was similar from other TGases such as human epidermal TGase was eluted at 0.2 M NaCl [Goldsmith and Martin 1995], and rat brain TGase was observed to be eluted at 0.28 M and 0.35 M of NaCl concentration [Kwak et al 1998]. The fi nal step of purifi cation was achieved *Based on 50 g rosemary.…”
Section: Purifi Cation Of Transglutaminasementioning
confidence: 99%
“…The theory can also explain why pathology is restricted to certain brain regions, despite wide-spread expression of mutated protein throughout the body in the various (CAG) n /Q n expansion diseases. Apparently, the rat brain contains at least two unique forms of tTGase [Kwak et al, 1998]. Moreover, recent work has shown that at least three transglutaminases, including tTGase, are present in the human brain .…”
Section: Implications For Neurodegenerative Diseasesmentioning
confidence: 99%